1111. Baricitinib versus Tocilizumab for Hospitalized Adults with Severe COVID-19 in a Community Health System: A Retrospective Cohort. (15th December 2022) - Gonzalez, Alexandra; Martinez, Aileen; Cardona, Lyssette L; Hernandez-Jimenez, Jarelys
Abstract: Background: Severe coronavirus disease 2019 (COVID-19) is associated with respiratory failure as well as thromboembolic and cardiovascular complications from dysregulated immune responses. Baricitinib (BAR), a Janus kinase (JAK) inhibitor, and tocilizumab (TZB), a monoclonal anti-interleukin-6 (IL-6) receptor antibody, earned Emergency Use Authorizations (EUA) from the Food and Drug Administration (FDA) for the treatment of COVID-19. This study aims to compare the effects of BAR and TZB in severe COVID-19. Methods: A retrospective chart review of patients admitted to Cleveland Clinic Martin Health with COVID-19 having received TZB or BAR was completed between 07/01/20 to 12/31/21. Exclusion criteria included patients who had received both agents in the same admission, received fewer than 5 doses of remdesivir, or were pregnant. The primary objective was to evaluate in-hospital mortality. For secondary outcomes, hospital length of stay (LOS), intensive care unit LOS, readmission due to respiratory-related causes, progression to mechanical ventilation (MV) and CRP levels upon discharge or death were assessed. Safety outcomes were described by incidences of superimposed bacterial infections, thrombosis, and herpes simplex virus reactivation. Results: After adjustment of sex and CRP level, the odds of death in TZB was 86% higher than that of BAR group (OR 1.86, 95%CI 1.17-2.96, p=0.009). TZB group had more females (45% vs. 34%, p=0.036) and longer LOS (median [IQR]: 15 [10, 23] vs. 13 [9, 20], p=0.0390). TZB group had more organ support (47% vs. 29%, p< 0.001), more ICU admission and longer ICU LOS, more MV progression and longer duration of MV (36% vs. 22%, p=0.007; 0[0, 9] vs. 0[0, 2], p< 0.001). TZB had more additional source of infection (25% vs. 16%, p=0.043) and more positive microbiology from blood (10% vs. 3%, p=0.009). Conclusion: Our findings suggest that BAR may have lower rates of in-hospital mortality when compared to TZB. TZB was also found to have higher needs for organ support. Superimposed infections, thrombosis, and HSV reactivation were similar in both groups. Larger randomized studies comparing these agents are needed. Disclosures: All Authors : No reported disclosures.